Enhancing Sound Governance Through Public Information Management:An Evaluation of PPID Performance - Arsa Ikhsani Asahara; Gerry Katon Mahendra (Jurnal Kebijakan Publik, 2026)
This study aims to evaluate the performance of the Information and Documentation Management Officer (PPID) in managing public information disclosure in Sleman Regency. Public information disclosure is a key indicator in achieving transparent, accountable, and participatory governance. However, monitoring and evaluation results by the Yogyakarta Special Region Information Commission indicate that the level of public disclosure by government agencies in Sleman Regency remains inconsistent, with some agencies not yet meeting the “informative” category. This study employs a descriptive qualitative approach with data collection techniques involving interviews and documentation. Research informants include the Regional Information Commission of the Special Region of Yogyakarta, the Communication and Information Technology Agency as the supervising body for PPIDs, and Regional Government Agencies as the implementing bodies. Data analysis utilizes public service performance indicators covering service quality, responsiveness, responsibility, and accountability. The results of the study indicate that the implementation of public information services has generally proceeded in accordance with regulations; however, challenges remain, such as limited human resources, suboptimal administrative management, and uneven capacity in information management. Therefore, institutional strengthening, enhancing human resource competencies, and optimizing the use of information technology are necessary to improve the quality of public information transparency services in Sleman Regency.